Coordination and thermodynamics of trivalent curium with malonate at increased temperatures: a spectroscopic and quantum chemical study - Skerencak-Frech, Andrej; Fröhlich, Daniel R.; Panak, Petra (Inorganic chemistry, 2017)
The complexation of Cm(III) with malonate is studied by time-resolved laser fluorescence spectroscopy (TRLFS) in the temperature range from 25 to 90 °C. Three complexes ([Cm(Mal)n]3-2n, n = 1, 2, 3) are identified and their molar fractions are determined as a function of the ligand concentration, the ionic strength, and the temperature. A general shift of the chemical equilibrium toward higher complexes with increasing temperature is observed, with the [CmMal3]3- complex forming only at T > 40 °C. The conditional stability constants (log K′n(T)) are calculated and extrapolated to Im = 0 with the specific ion interaction theory (SIT). The log Kn0(T) values increase by 0.25 to 0.5 logarithmic unit in the studied temperature range. The temperature dependency of the log K°n(T) is fitted by the integrated Van’t Hoff equation, yielding the thermodynamic functions ΔrH°m and ΔrS°m. The results show positive reaction enthalpies and entropies for each complexation step. While the ΔrH°n values are constant within their error range, the ΔrS°n values decrease successively with each ligand added. To explain this effect, quantum chemical calculations of binding energies and bond lengths of the different Cm(III) malonate species are performed. The results show that malonate is capable of stabilizing its end-on coordination mode to some extent by forming hydrogen bonds to first-shell water molecules. As a result, an equilibrium between side-on and end-on coordinated malonate ligands is present, with the latter becoming more pronounced for the higher complexes due to steric reasons.